Penerapan Model Quantum Teaching untuk Meningkatkan Minat Belajar IPAS Siswa Kelas V MIS Nurul Yaqin - Lulu Pebri Dewi; Sri Yulia Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Learning interest is the tendency of students to engage in learning activities driven by the desire to achieve optimal results. However, the learning interest of fifth-grade students at MIS Nurul Yaqin remains low. This study aims to enhance students' learning interest in IPAS subjects through the implementation of the Quantum Teaching and Learning model, which focuses on teachers' management of the learning process, from planning and instruction to evaluation. The research method used is the Kemmis and McTaggart action research model, which consists of four stages. The findings indicate that teacher activity increased from 73% in cycle I to 91% in cycle II, classified as very good. Similarly, student activity improved from 70.53% in cycle I to 86.25% in cycle II, also categorized as very good. These results demonstrate that the implementation of the Quantum Teaching and Learning model effectively enhances students' learning interest in IPAS subjects in fifth grade at MIS Nurul Yaqin.